Challenges Related to Seabed Soil Conditions in Offshore Engineering in China: Findings from Site Investigations - Xiaoqing Wu; Youkou Dong; Kuanjun Wang; Kanmin Shen; Hongyi Yang (Journal of Marine Science and Engineering, 2025)
Seabed-related issues are common in offshore areas. This poses significant challenges for the design and construction of offshore engineering projects. Under unfavourable seabed soil conditions, foundations may fail to meet the load-bearing capacity requirements, resulting in severe settlement and tilting and, ultimately, the failure of offshore structures. Despite the critical nature of these challenges, a comprehensive literature review for the identification and risk analysis of various unfavourable seabed soil conditions is currently lacking. This paper provides an overview of five key challenges related to seabed soil conditions in China, namely thick, soft mud layers; shallow gas and pockmarks; sand liquefaction; dense sand layers; and boulder stones. The formation mechanisms, distribution areas and engineering characteristics of these conditions are discussed in detail, integrating insights from previous research. Data from site investigations of real-world offshore engineering projects are presented, based on which risk assessment is conducted. This study not only enhances our understanding of the identification, distribution and hazards associated with various unfavourable seabed soil conditions in offshore engineering but also offers guidance on utilizing investigation data for effective risk assessment.